Analysis of the metabolic and hormonal effects of Krav Maga physical training - Andrade Neto, Joao Batista de; Navarro, Antonio Coppi; Navarro, Francisco; Salgado Filho, Natalino (Open Science Journal, 2022)
Abstract Aim: The aim of this study is to evaluate the metabolic aspects and cortisol during the practice of this modality. Methods A sample of 30 volunteers was distributed into a group of beginners who had never practiced the modality (GI; n = 15). The experimental group consisted of veteran Krav Maga practitioners (GV; n = 15). Both participated in training for a period of 16 weeks and samples were collected in week 1, 8 and 16 (S1, S8 and S16, respectively), always at the same time. Pre- and post-training glycemic behavior, fasting glucose, lipid profile (total cholesterol, HDL cholesterol, LDL, VLDL, triglycerides), basal lactate and cortisol were measured. Results: The variables total cholesterol, triglycerides, HDL, LDL and cortisol did not present significant differences with the training time and between GI and GV. On the other hand, fasting glucose, post-training glucose and VLDL showed a significant effect (p = 0.003; p < 0.001 and p < 0.001, respectively) related to training time, however, there was no difference between GI and GV Pre-training glucose increased with training time (p < 0.001) and was higher for GV. Conclusion: The practice of Krav Maga for 16 weeks promotes changes related to training time for fasting glucose and pre- and post-training glucose, along with VLDL